Determinación de la digestibilidad in vivo de microsilos de taralla de maíz con la adición de dos aditivos; urea y maguey pulquero (Agave salmiana) para la alimentación de cuyes (Cavia porcellus)” - Pucha Pauta, Olger Vinicio (2017)
The present research was developed in the Experimental Experimental Punzara of the National University of Loja, with the purpose of determining the in vivo digestibility of cornilica microsilica with the addition of two additives; Urea and honey of Maguey pulquero (Agave salmiana); For the effect, three treatments were defined with the addition of 2% of Agave salmiana, 3% of urea with the control with 0% of additives. We used 9 male guinea pigs type 1 with an average weight of 800 gr; the food supply was in the morning and in the evening; we used a Latin square design with three treatments, three replicates at three different times. The variables of study were the chemical composition, realized through the proximal analysis of Weende; And, in vivo digestibility. For the statistical analysis a mixed model was used, in which the fixed main effects were the diets, the time and their interaction and the random effect is the animal nested to the ration. Silage with the addition of 2% of urea showed a better nutritional profile; No differences were detected between treatments for dry matter and protein digestibility (P≥0.62). An average for dry matter of 77.46% and crude protein of 79.97% was obtained. It was concluded that the inclusion of additives in the production of silage makes it possible to improve the nutritional profile of the same.